Influence of Synthesis Conditions on Crystal Structure and Catalytic Performance of CoFe₂O₄ Nanoparticles for Tetracycline Degradation by Persulfate Activation Process - Tuan, Phan Anh; Tran, Pham Bao; Cuc, Nguyen Thi; Anh, Le Quynh; Trinh, Tran Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4DO - 10.25073/2588-1140/vnunst.5921, 2025)
In this research, CoFe 2 O 4 nanoparticles were systematically synthesized by hydrothermal method, under different synthesis conditions such as variations in pH of the mixture, in reaction time, and in temperature, to study the impact of synthesis conditions on crystal structure and catalytic performance of CoFe 2 O 4 nanoparticles. The catalytic performance was evaluated though the degradation of tetracycline (TC) using persulfate activation process to figure out the optimal synthesis conditions. The latter were then applied to produce CoFe 2 O 4 nanoparticles which were subsequently applied for studying the TC degradation process. The obtained results revealed that CoFe 2 O 4 nanoparticles were successfully produced without significant impurities. pH of the mixture, reaction time, and temperature all contributed to changes in particle size, crystallinity as well as the catalytic performance. Under optimal synthesis conditions (pH 11.0, 180 °C, 12 hour), 66.1% of 10 mg/L TC solution were removed after 60 min. The TC degradation process followed the pseudo-second kinetics model, with R 2 ranging from 0.933 to 0.987, and k values within the range of 0.001 – 0.01 mg·L -1 ·min -1 . Thes findings highlight the potential use of CoFe 2 O 4 catalyst for wastewater treatment application. This research provides a simple approach to design and synthesis of CoFe 2 O 4 magnetic catalysts for the treatment of antibiotic resdues in water.